Impact of Work Life Balance on Working Women: An Overview - Sigroha , Anju; Girdhar , Yogita; Sangwan , Sneha (Gyan Management Journal, 2011)
Female participation in the workplace has grown dramatically over the past couple of decades. This growth has been especially noticeable in the professional and managerial fields where women now occupy a significant number of positions. The increased female workforce participation has been accompanied by its own challenges like managing time, roles & responsibilities at workplace & at home. Work life balance is seen more as women issue due to the traditional mindset, where the woman is considered primarily responsible for the smooth running of the day to day affairs of the family irrespective of her job profile and official responsibilities. However, over the years, women have started receiving support& understanding at home, especially from their spouses. Nonetheless, there are some unspoken challenges which need to be dealt with constantly. If family responsibilities are allowed to interfere with work responsibilities on a regular basis, it may hinder women’s career progression, lower the job satisfaction levels, result in lack of concentration at work, increase absenteeism & may eventually lead to turnover. No matter how well they prove themselves, women find it increasingly difficult to climb up the career ladder as they are perceived to be more committed towards family than workplace. Even at family front, a working woman has to always face the notion of not being there when there family needs them. This article examines the challenges faced by working women in establishing & sustaining work-life balance and also outlines the factors that could help to create a healthy work-life balance for working women.